2006
DOI: 10.1007/s00381-006-0175-7
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in survivors of childhood brain tumours

Abstract: We observed that most of the patients had a BMD that was lower than normal in both the lumbar column and in the femoral neck. Bone mass loss was higher in the lumbar region rather than in the femoral neck, due to spinal radiation therapy and to the effect of hormonal deficiencies. Particularly hypogonadism, but also multiple hormonal deficiencies, are associated with lower BMD values. Experience in clinical care of these patients suggests the importance of periodic evaluations of BMD, especially in those with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
2
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 28 publications
4
20
2
1
Order By: Relevance
“…In conclusion, we found that 67.9% of the iGCTLS had a BMD less than −1 SD, which is a higher percentage than expected, based on the World Health Organization's report [39] and survivors of other types of brain tumor [9,10,13,20,21]. The main reason might be radiation therapy and the high prevalence of GHD.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…In conclusion, we found that 67.9% of the iGCTLS had a BMD less than −1 SD, which is a higher percentage than expected, based on the World Health Organization's report [39] and survivors of other types of brain tumor [9,10,13,20,21]. The main reason might be radiation therapy and the high prevalence of GHD.…”
Section: Discussionmentioning
confidence: 52%
“…In this study, 25.0% of the iGCTLS had osteoporosis, and 42.9% had osteopenia in all ROI. Previous studies have reported a high prevalence of BMD deficits in survivors of childhood malignancy, including brain tumors [10,13,[19][20][21]. Both the tumor itself and its treatment potentially encompass risk factors for BMD deficits such as high cumulative doses of steroids, methotrexate, cranial radiation, and testicular radiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sex hormone/sex steroid deficiencies may contribute to lowering bone mineral content and osteopenia in childhood cancer survivors. 33 Development of a pubertal disorder is common in pediatric patients after prepubertal H-P axis irradiation and can occur after cranial irradiation up to 2 years earlier in both sexes. 34 Often, the thyroid hormone and ACTH deficiencies are subtle and dominated by overt and more severe symptoms of other hormonal deficiencies.…”
Section: Hormonal Deficiencies and Clinical Implicationsmentioning
confidence: 99%